Sports and Mass Events at the School - Tuychiev Ashurali; Rakhmonov Doston (Genius Journals, 2023)
Extra-curricular sports and health-improving work becomes an integral part of the pedagogical process aimed at educating a comprehensively physically and spiritually developed personality. This is facilitated by the organization and holding of mass sports events.
Keywords: Sports and physical culture events; junior school age; middle school age